The Impact of Foreign Direct Investments on the Economic Growth and Export Potential of Albania - Vangjeli, Alketa (Mediterranean Journal of Social Sciences, 2012)
Foreign Direct Investments (FDI) has a positive impact upon the economic growth in the receiving countries. The countries intransition need FDI not just to produce more goods and a higher quality. Foreign capital investments are the most efficient and safe wayto integrate into the world economy. FDI would allow the re-specialization of the economy to surpass the situation of maintaining on theworld markets only with food products and raw materials. Indeed, the acquired experience shows that FDI plays a determinant role inrespecialising the transition economies and in increasing the export potential. A transition country like Albania is assumed to benefit fromFDI not only by supplementing domestic investment, but also in terms of employment creation, transfer of technology, increaseddomestic competition and other positive externalities. Albania offers attractive investment opportunities for foreign companies and hasadopted a number of policies to attract FDI into the country and the country seems to offer perhaps one of the most liberal FDI regimesin region. Our analysis in this paper, based on economic evidence over recent years, indicates that FDI and trade contribute significantlytowards advancing economic growth in Albania. Further, we shall examine some structural changes which occurred under the influenceof FDI in the Albanian economy and in Balkan region, drawing also the attention upon the changes in the export potential of thosecountries.